QRIS Adoption and Car Salon Business Sustainability: The Mediating Role of Customer Satisfaction - M. Khusaini; Danial Thaib (Indonesian Journal Publisher, 2026)
This study aims to examine the effect of financial technology and QRIS-based digital transaction processes on business sustainability, with customer satisfaction serving as a mediating variable. This research employs a quantitative approach using a survey method. Data were collected from 100 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that financial technology and QRIS-based digital transactions significantly influence customer satisfaction. Customer satisfaction shows the strongest effect on business sustainability. Moreover, customer satisfaction significantly mediates the relationship between digital financial technology, transaction processes, and business sustainability. In conclusion, the sustainability of car salon businesses is strongly determined by customer satisfaction achieved through effective digital financial technology implementation. This study introduces a sector-specific empirical model that explains how customer satisfaction mediates the relationship between FinTech (QRIS) adoption and business sustainability in the car salon industry in Jakarta. Unlike prior MSME-focused studies, it provides new evidence from a niche service sector using PLS-SEM to reveal the dominant indirect effect of digital transactions on long-term business continuity.